Capture and simulation of the ocean environment for offshore renewable energy. (April 2019) - Draycott, S.; Sellar, B.; Davey, T.; Noble, D.R.; Venugopal, V.; Ingram, D.M.
Abstract: The offshore renewable energy sector has challenging requirements related to the physical simulation of the ocean environment for the purpose of evaluating energy generating technologies. In this paper the demands of the wave and tidal energy sectors are considered, with measurement and characterisation of the environment explored and replication of these conditions described. This review examines the process of advanced ocean environment replication from the sea to the tank, and rather than an exhaustive overview of all approaches it follows the rationale behind projects led, or strongly connected to, the late Professor Ian Bryden. This gives an element of commonality to the motivations behind marine data acquisition programmes and the facilities constructed to take advantage of the resulting datasets and findings. This review presents a decade of flagship research, conducted in the United Kingdom, at the interfaces between physical oceanography, engineering simulation tools and industrial applications in the area of offshore renewable energy. Wave and tidal datasets are presented, with particular emphasis on the novel tidal measurement techniques developed for tidal energy characterisation in the Fall of Warness, Orkney, UK. Non-parametric wave spectra characterisation methodologies are applied to the European Marine Energy Centre's (EMEC) Billia Croo wave test site, giving complex and highly realistic site-specific directional inputs for simulation of wave energy sites and converters. Finally, the processes of recreating the resulting wave, tidal, and combined wave-current conditions in the FloWave Ocean Energy Research Facility are presented. The common motivations across measurement, characterisation, and test tank are discussed with conclusions drawn on the strengths, gaps and challenges associated with detailed site replication. Abstract : Highlights: State-of-the-art review of ocean measurement, analysis, and replication techniques. Decade of flagship research presented, led by the late Professor Ian Bryden. Novel measurement techniques presented for tidal site characterisation. Advanced ocean replication methodologies described, with recent results presented.